Physical activity and sedentary behaviour in a residential aged care facility - Parry, Sharon; Chow, M.; Batchelor, F.; Fary, Robyn (Wiley-Blackwell Publishing Asia, 2019)
© 2018 AJA Inc. Objective: To evaluate sedentary behaviour and physical activity levels in independently mobile older adults with and without dementia living in residential aged care. Methods: Sedentary behaviour and physical activity were measured in 37 residents of an aged care facility using an accelerometer worn during waking hours for five days. Results: Participants with valid accelerometer data (n = 28) spent 85% of the time sedentary, and 12% in low-intensity, 2% in light-intensity and 1% in moderate-to-vigorous-intensity physical activity. Over half of sedentary time was accumulated in bouts of greater than 30 minutes. Physical activity at any level of intensity was performed in bouts of less than 10 minutes. Conclusion: Residents were highly sedentary and inactive. In particular, the short duration of each bout of activity amongst lengthy periods of sedentary behaviour was a substantial finding. The study suggests the need to develop innovative ways of breaking up sedentary behaviour in residential aged care.